Tough Trucks Activity Book - Mitton, Tony (London Pan Macmillan, 2016)
There are puzzles and mazes as well as join the dots, counting and colouring - all featuring your favourite trucks. Get busy with the vehicle stickers... and you can build your very own TOUGH TRUCK. Press out the vehicle piece inside the cover. You won't need scissors or glue, but you will need some help from an adult.
Shelving Location Pop-up Book Section
Keywords: Activity Book